A waiting time based discrete event-triggered control for networked switched systems with actuator saturation. (August 2020) - Qi, Yiwen; Xu, Xindi; Lu, Shaowei; Yu, Yongtao
Abstract: This paper studies the event-triggered control problem for networked switched systems with actuator saturation. An event-triggering strategy is developed based on discrete event-triggered samplings. By which, a waiting time is first ensured to avoid the Zeno-like behavior, and then the data transmission is carried out once a desired performance-dependent condition is satisfied. According to the implementation of the triggering strategy and considering the impacts of transmission delay and actuator saturation, a time-delay closed-loop switched system is developed. Subsequently, sufficient conditions to ensure stability of the closed-loop system are derived by making use of the average dwell time and multiple Lyapunov functions method. In particular, since the waiting time, periodic sampling instants, data updating instants and switching instants may be coupled with each other, typical cases are discussed thoroughly to analyze the system stability. Moreover, together with the estimation of domain of attraction, sufficient conditions for the design of the desired state-feedback sub-controller gains and event-triggering parameters are presented. Finally, the effectiveness of the proposed method is verified by numerical simulations.